SERS (Surface Enhanced Raman Scattering) sensor based on Ti3C2Tx / (001) TiO2 / W18O49 composite heterostructure and application of SERS sensor

Through the SERS sensor based on Ti3C2Tx/(001)TiO2/W18O49 composite heterostructure, the problem of insufficient detection sensitivity of nanoplastics and microplastics in the prior art is solved, and high sensitivity detection and multi-component analysis of PS microplastics are realized, which is suitable for detection applications in actual environments.

CN119666811AActive Publication Date: 2025-03-21HEFEI UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411413526.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-03-21
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The lack of efficient and accurate nanoplastic and microplastic detection substrates in the prior art leads to insufficient detection sensitivity and difficulty in rapid on-site detection.

Method used

Using a SERS sensor based on Ti3C2Tx/(001)TiO2/W18O49 composite heterostructure, the exposed TiO2 on the multi-layer Ti3C2Tx MXene surface was grown in situ by sodium fluoroborate as a crystal surface control agent, and W18O49 was epitaxially grown to form a semiconductor heterojunction to prepare a three-dimensional SERS sensor.

Benefits of technology

The detection sensitivity of rhodamine 6G is achieved to reach 10-8M, the enhancement factor (EF) is 2.33×106, and the detection sensitivity of polystyrene (PS) microplastics is as low as 25μg/mL. It can accurately identify and resolve multi-component micro/nanoplastic mixtures, and successfully detect PS microspheres in rainwater, soil and industrial wastewater in actual environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119666811A_ABST
    Figure CN119666811A_ABST
Patent Text Reader

Abstract

The invention discloses an enhanced Raman scattering (SERS) sensor based on a Ti3C2Tx / (001) TiO2 / W18O49 composite heterostructure and application of the SERS sensor, and relates to the technical field of micro-plastics and nano-plastics, and the SERS sensor is prepared by the following steps: dissolving LiF in HCl, stirring, adding Ti3AlC2, carrying out water bath reaction, centrifuging, washing, collecting Ti3C2Tx MXene precipitate, drying, dispersing in deionized water, adding NaBF4 and HCl, stirring, carrying out ultrasonic treatment, reacting, filtering, washing, and drying to obtain the SERS sensor based on the Ti3C2Tx / (001) TiO2 / W18O49 composite heterostructure, thus obtaining the SERS sensor based on the Ti3C2Tx / (001) TiO2 / W18O49 composite heterostructure. And centrifugally washing and drying to obtain the Ti3C2Tx / (001) TiO2 powder. And adding the obtained Ti3C2Tx / (001) TiO2 powder into isopropanol, adding WCl6, stirring, reacting in a reaction kettle, carrying out centrifugal washing, carrying out suction filtration on the Ti3C2Tx / (001) TiO2 / W18O49 on a cellulose filter membrane, drying, and manufacturing the three-dimensional SERS sensor by using a puncher. The detection limit of the sensor on polystyrene (PS) particles is 25 mu g / mL, strong linear correlation (R2 = 0.98) is shown, and the sensor can be used for analyzing an MNPs mixture of three components of PS, polyethylene (PE) and polypropylene (PP) and quantitatively detecting PS microplastics in rainwater, soil and industrial wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of microplastics and nanoplastics, and in particular to a Ti3C2T x / (001)TiO2 / W 18 O 49 Composite heterostructure SERS sensors and their applications. Background Art

[0002] The widespread industrial production and use of plastics has brought convenience and diversity to many aspects of human life. However, this widespread use has also led to a significant increase in plastic pollution. Over time, after discarded plastics undergo environmental weathering and degradation processes, larger plastic fragments will break down into smaller microplastics (MPs, 1μm to 5mm) and nanoplastics (NPs, less than 1000nm), collectively referred to as micro / nanoplastics (MNPs). These MNPs are easily diffused in a variety of environmental media such as air, water and soil. The accumulation of these particles in human tissues may have adverse effects on organ systems and overall health.

[0003] Currently, the methods used to detect MNPs include a variety of analytical techniques such as microscopy, thermal analysis, and spectroscopy, each of which has its own unique advantages and limitations. Microscopy can provide valuable morphological information of MNPs, but its disadvantages are that it does not have the ability to detect MNPs quickly on site and cannot directly distinguish multi-component MNPs. Thermal analysis is usually used in combination with other techniques, mainly including pyrolysis-gas chromatography-mass spectrometry (py-GC-MS) and thermogravimetric-mass spectrometry (TGA-MS). Although these methods are very practical, they generally have the disadvantages of being time-consuming, destructive, and lacking morphological information. Fourier transform infrared spectroscopy (FTIR) can characterize the chemical composition of MNPs non-destructively, however, this method requires sample pretreatment, which is not conducive to rapid on-site analysis. Raman spectroscopy is a reliable method for characterizing the structure and chemical composition of MNPs that only requires a small amount of sample, but its relatively low sensitivity limits its widespread application. Therefore, it is necessary to develop analytical methods that are both convenient and fast and have high sensitivity to achieve effective detection of MNPs in the environment.

[0004] Surface enhanced Raman scattering (SERS) is a detection technique known for its high sensitivity. SERS technology has shown wide application potential in multiple disciplines such as environmental monitoring and biosensing due to its ability to provide molecular fingerprints, non-destructive detection, and the ability to analyze multiple components simultaneously. There are two main SERS enhancement mechanisms: electromagnetic field enhancement (EM) and chemical enhancement (CM). The EM effect mainly originates from the localized surface plasmon resonance (LSPR) phenomenon, which is caused by the excitation of noble metal nanoparticles on the rough substrate surface, while the CM effect is the result of chemical interactions between the substrate and the adsorbed molecules on the surface. SERS technology has become a very promising method for detecting MNPs. For example, Zhang et al. successfully achieved the detection of nanoplastics at a concentration of μg / L by utilizing the aggregation effect between silver nanoparticles (Ag NPs) and plastic particles. Similarly, the Li group prepared AgNPs@PMMA films through a liquid-liquid interface self-assembly method, which enabled the simultaneous detection of polystyrene (PS) and polyethylene terephthalate (PET) nanoplastic particles at very low concentrations. Huang and co-workers employed an electrostatic adsorption strategy to achieve detection of 0.08 wt% PS NPs between oppositely charged Au NPs and PS NPs. Despite these remarkable advances, the detection sensitivity of MNPs still largely depends on the electromagnetic field enhancement provided by the substrate composed of noble metals.

[0005] MXene is a new type of two-dimensional transition metal carbon / nitrogen or carbon nitride material. It has attracted widespread attention in the scientific community due to its unique layered structure, excellent hydrophilicity and strong adsorption properties. These properties have promoted the widespread application of MXene in many fields such as environmental remediation, sensing technology, energy storage and catalytic processes. In the field of SERS technology, MXene is gradually becoming a very promising SERS substrate material. For example, the Dang group developed flexible MXene / Au nanocubes (Au NCs) and TiVC-OH-Au sensors to enhance SERS sensitivity by enriching analytes, thereby enabling sensitive detection of biomarkers in human body fluids. In addition, Peng et al. reported Ag / Nb2CT for the detection of MNPs. xMXene substrate, which achieved a detection limit of PS as low as 10μg / mL and demonstrated its ability to distinguish two-component nanoplastic mixtures. However, MXene materials are currently mainly used as carriers of noble metal nanoparticles. In existing literature reports, the integration of MXene with semiconductor materials as SERS substrates, especially for the detection of MNPs, is still a relatively new field. In air and pressurized water environments, Ti atoms in MXene are oxidized to anatase TiO2 nanocrystals. At present, the composite SERS substrate based on MXene noble metals is mainly due to the EM enhancement of noble metals, while the SERS enhancement effect of MXene is weak, and Ti atoms in air and pressurized water environments are oxidized to anatase TiO2 nanocrystals, which limits its application as a SERS substrate alone. Summary of the invention

[0006] The purpose of this application is to provide a Ti3C2T x / (001)TiO2 / W 18 O 49 The SERS sensor with a composite heterostructure solves the technical problem of the lack of a more efficient and accurate detection substrate for nanoplastics and microplastics in the prior art.

[0007] The present application provides a Ti3C2T x / (001)TiO2 / W 18 O 49 Composite heterostructure SERS sensor based on Ti3C2T x / (001)TiO2 / W 18 O 49 The preparation method of the composite heterostructure SERS sensor is as follows:

[0008] Step 1: Dissolve LiF in HCl solution and stir, then add Ti3AlC2, react in a water bath, centrifuge the mixture, wash with deionized water until the pH value of the supernatant is in the range of 6.8-7.2, collect the lower layer Ti3C2T x MXene precipitation and drying to obtain multilayer Ti3C2T x MXene powder;

[0009] Step 2: The multilayer Ti3C2T x MXene powder was dispersed in 1M hydrochloric acid solution, and NaBF4 was added as a crystal surface control agent. After stirring for 30 minutes, ultrasonic treatment was performed, and the mixture was reacted in a reactor at 160°C for 12 hours. After the reaction, the mixture was cooled and centrifuged. The precipitate was washed with deionized water and dried to obtain Ti3C2T x / (001)TiO2 powder;

[0010] Step 3: The Ti3C2T x / (001)TiO2 powder was added to the isopropanol solution, WCl6 was added to the obtained suspension, and the mixture was stirred and reacted in the reactor. After the reaction, the precipitate was centrifuged and washed by vacuum filtration to separate Ti3C2T x / (001)TiO2 / W 18 O 49 Filter on a cellulose filter membrane and let it dry naturally. Use a punch to make three-dimensional Ti3C2T x / (001)TiO2 / W 18 O 49 SERS sensor.

[0011] Preferably, in step 1, the water bath reaction time is 24 hours, the water bath reaction temperature is 35° C., the centrifugation condition is centrifugation at a speed of 3500 revolutions per minute for 5 minutes, and the drying condition is vacuum drying at 60° C.

[0012] Preferably, in step 2, the centrifugation condition is centrifugation at 4000 rpm for 5 min.

[0013] Preferably, in step three, the reaction conditions in the reactor are reaction at 200° C. for 20 h, and the centrifugation conditions are centrifugation at 5000 rpm for 7 min.

[0014] Preferably, in step three, the specific steps of washing are washing twice with anhydrous ethanol and then washing once with deionized water.

[0015] The present application provides a method based on the Ti3C2T x / (001)TiO2 / W 18 O 49 Application of composite heterostructure SERS sensors in microplastics and nanoplastics.

[0016] Preferably, based on Ti3C2T x / (001)TiO2 / W 18 O 49 The SERS sensor with the composite heterostructure can detect PS particles at a concentration of at least 25 μg / mL and rhodamine at a minimum concentration of 10 -8 M.

[0017] Preferably, based on Ti3C2T x / (001)TiO2 / W 18 O 49The composite heterostructured SERS sensor is used to analyze micro / nanoplastic mixtures of PS, PE and PP, and is used for the quantitative detection of PS microplastics in rainwater, soil and industrial wastewater.

[0018] Therefore, this application adopts the above-mentioned Ti3C2T x / (001)TiO2 / W 18 O 49 The composite heterostructure SERS sensor has the following beneficial effects: by using sodium fluoroborate as a crystal surface control agent, the multilayer Ti3C2T x TiO2 with (001) crystal plane exposed is directly grown on the MXene surface in situ, and W is epitaxially grown 18 O 49 , forming a semiconductor heterojunction. By vacuum filtration, Ti3C2T x / (001)TiO2 / W 18 O 49 The three-dimensional SERS sensor was prepared by filtration on a cellulose filter membrane. The three-dimensional SERS sensor showed excellent detection sensitivity, with the detection sensitivity of rhodamine 6G (R6G) probe molecules as low as 10 -8 M, the corresponding enhancement factor (EF) is 2.33×10 6 In addition, the detection sensitivity of the SERS sensor for PS was as low as 25 μg / mL. Using its fingerprint recognition characteristics, the sensor successfully identified multi-component mixed MNPs of PS, PE and PP. In practical application environments, the three-dimensional SERS sensor developed in this study successfully detected trace amounts of PS microspheres in rainwater, soil and industrial wastewater, highlighting its potential in practical environmental monitoring. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The three-dimensional Ti3C2T x / (001)TiO2 / W 18 O 49 Schematic diagram of the preparation process of SERS sensor and SERS detection of micro / nano plastics;

[0020] Figure 2 In the figure, (a) is the SEM image of Ti3AlC2 MAX phase; (b) is the SEM image of Ti3C2T x SEM image of MXene; (c) Ti3C2T x / (001) SEM image of TiO2; (d) SEM image of Ti3C2T x / (001)TiO2 / W 18 O 49 SEM image of Ti3C2Tx / (001)TiO2 / W 18 O 49 SEM images of PS microplastic particles on the substrate; (f) and (g) are Ti3C2T x / (001)TiO2 / W 18 O 49 HRTEM image of Ti3C2T x / (001)TiO2 / W 18 O 49 SAED images of Ti3C2T x / (001)TiO2 / W 18 O 49 Element mapping map;

[0021] Figure 3 (a) is Ti3C2T at 120℃ x / (001) SEM image of TiO2; (b) SEM image of Ti3C2T at 140℃ x / (001) SEM image of TiO2; (c) Ti3C2T at 160℃ x / (001) SEM image of TiO2; (d) SEM image of Ti3C2T at 180℃ x / (001) SEM image of TiO2; (e) SEM image of Ti3C2T when WCl6 addition amount is 30mg x / (001)TiO2 / W 18 O 49 SEM image of Ti3C2T when WCl6 addition amount is 40mg x / (001)TiO2 / W 18 O 49 SEM image of Ti3C2T when WCl6 addition amount is 50mg x / (001)TiO2 / W 18 O 49 SEM image of Ti3C2T when WCl6 addition amount is 60mg x / (001)TiO2 / W 18 O 49 SEM images of Ti3C2T x / (001) SERS performance of TiO2 at different reaction temperatures; (k) and (l) are Ti3C2T x / (001)TiO2 / W 18 O 49 SERS performance of substrates at different WCl6 dosages;

[0022] Figure 4 In the figure, (a) shows different synthesized samples of Ti3C2T x MXene, Ti3C2T x / (001)TiO2、W 18 O 49 and Ti3C2T x / (001)TiO2 / W 18 O 49 UV-visible absorption spectra of 10 detected in different synthetic samples; (b) -5 SERS spectrum of MR6G; (c) SERS spectrum of Ti3C2T under laser irradiation x MXene, TiO2 and W 18 O 49 Schematic diagram of the charge transfer process between

[0023] Figure 5 (a) is the SERS spectra of R6G at different concentrations; (b) is the SERS spectra of PS at different concentrations (from 25 μg / mL to 1000 μg / mL); (c) is the SERS spectra of PS at 1002 cm -1 The relationship between the SERS intensity of the characteristic peak and its concentration; (d) is the SERS spectrum of 250 μg / mL PS at 30 different points; (e) is the SERS spectrum of PS at 1002 cm -1 SERS intensity distribution scatter plot of characteristic peaks; (f) is a three-dimensional Ti3C2T x / (001)TiO2 / W 18 O 49 Durability testing of SERS sensors;

[0024] Figure 6 In the figure, (a) is the SERS spectrum of single-component plastics (PS, PE and PP); (b) is the SERS spectrum of multi-component plastics (PS and PE; PS and PP; PE and PP; PS, PE and PP).

[0025] Figure 7 In the figure, (a) and (b) are the SERS spectra and linear fitting curves of PS microspheres (800 nm) prepared from rainwater, an actual environmental sample; (c) and (d) are the SERS spectra and linear fitting curves of PS microspheres (800 nm) prepared from soil; (e) and (f) are the SERS spectra and linear fitting curves of PS microspheres (800 nm) prepared from industrial wastewater;

[0026] Figure 8 W 18 O 49 SEM images of

[0027] Fig. 9Ti3C2T x / (001)TiO2 / W 18 O 49 EDS element diagram;

[0028] Fig.10 Ti3C2T x MXene, Ti3C2T x / (001)TiO2、W 18 O 49 and Ti3C2T x / (001)TiO2 / W 18 O 49 XRD diffraction pattern;

[0029] Fig.11 is the calculation result of SERS enhancement factor (EF). DETAILED DESCRIPTION

[0030] Example 1

[0031] Material

[0032] Lithium fluoride (LiF, purity 99.0%), sodium fluoroborate (NaBF4, purity 99.0%), isopropanol (purity 99.0%), and tungsten chloride (WCl6, purity 99.0%) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Hydrochloric acid (HCl, mass fraction 36.0-38.0%) was purchased from Sinopharm Chemical Reagent Co., Ltd. Titanium aluminum carbide (Ti3AlC2, 400 mesh, purity 99.9%) was purchased from Foshan Xinxin Technology Co., Ltd. Polystyrene (PS, diameter 800nm) plastic dispersion was purchased from Yiyuan Biotechnology Co., Ltd. Polystyrene (PE) and polyethylene (PE) dispersions were purchased from Zhongke Leiming (Beijing) Technology Co., Ltd. All reagents and materials were not further purified.

[0033] Step 1: Accurately weigh 1.0g LiF and add it to a polytetrafluoroethylene (PTFE) reaction vessel containing 20mL 9M HCl. Stir the mixture for 10 minutes to ensure that LiF is completely dissolved. Subsequently, gradually add 1.0g Ti3AlC2, then place the reaction vessel in a water bath and continue stirring at 35°C for 24 hours. After the reaction is complete, centrifuge the mixture at 3500 revolutions per minute (rpm) for 5 minutes, then wash with deionized water until the pH value of the supernatant is in the range of 6.8-7.2. Collect the lower layer of Ti3C2T x MXene was precipitated and dried in vacuum at 60 °C to obtain multilayer Ti3C2T x The MXene powders were stored in a refrigerator at low temperature (5 °C) for subsequent experiments.

[0034] Step 2: Accurately weigh 100 mg of multilayer Ti3C2T x MXene powder was dispersed in 24 mL 1 M HCl until completely dissolved, and then 0.2635 g NaBF4 was added as a crystal face controller. The solution was then stirred for 30 min, ultrasonicated for 10 min, and then transferred to a 50 mL PTFE reactor and reacted at 160 ° C for 12 h. After the reaction was completed, the reactor was allowed to cool naturally to room temperature, and then the solution was centrifuged at 4000 rpm for 5 min, and the precipitate was washed twice with deionized water to remove residual reactants or impurities. The resulting precipitate was dried in an oven at 60 ° C to obtain Ti3C2T x / (001)TiO2 powder.

[0035] Step 3: Add 40mgTi3C2T x / (001)TiO2 powder was added to 20mL isopropanol and stirred thoroughly to achieve uniform dispersion. Subsequently, 40mgWCl6 was added to the suspension and stirred for 2h. The solution was then transferred to a 50mL PTFE reactor and reacted at 200℃ for 20h. After the reaction, the reactor was allowed to cool naturally to room temperature. The product was then centrifuged at 5000rpm for 7min. The precipitate was washed twice with anhydrous ethanol and once with deionized water. Subsequently, Ti3C2T x / (001)TiO2 / W 18 O 49 The cellulose membrane was filtered and allowed to dry naturally, and a commercial punch was used to make a circular three-dimensional Ti3C2T x / (001)TiO2 / W 18 O 49 SERS sensor, used for subsequent SERS detection.

[0036] 1. Material Characterization

[0037] Scanning electron microscopy (SEM) images were obtained by Gemini SEM 300; TESCAN MIRA3. The UV-visible absorption spectra of the samples were measured using a PuxiTU-1950 spectrophotometer. X-ray diffraction (XRD) patterns were recorded using a fixed target X-ray diffractometer (PANalytical X-Pert PRO MPD). High-resolution transmission electron microscopy (HRTEM) images and energy dispersive X-ray spectroscopy (EDS) analysis were performed using a Talos F200X G2.

[0038] 2. SERS detection

[0039] The SERS spectra were obtained by a micro-confocal Raman spectrometer (Thermo DXR2) equipped with a 532 nm laser wavelength. During the measurement, the laser power was set to 2 mW and a 50× objective lens was used to obtain the best signal intensity. When analyzing the standard solution and the actual sample, 20 μL and 30 μL of the solution to be tested were dropped onto the three-dimensional Ti3C2T x / (001)TiO2 / W 18 O 49 On the SERS sensor, SERS detection was performed after the sample was dried. When analyzing the data, all SERS spectra were baseline corrected to reduce the interference of ambient stray light, thereby improving the accuracy and reliability of spectral analysis.

[0040] Ti3C2T x / (001)TiO2 / W 18 O 49 Characterization

[0041] LiF and HCl were used to selectively etch the Al layer in the Ti3AlC2 MAX phase, and then a simple hydrothermal method was used to synthesize the multilayer Ti3C2T x TiO2 was in situ grown on MXene. Subsequently, Ti3C2T x W epitaxially grown on the (001)TiO2 composite material 18 O 49 Nanostructure. Figure 1 It intuitively shows that Ti3C2T x / (001)TiO2 / W 18 O 49 Synthetic routes to composite structures. Figure 2 (a) shows the SEM image of the Ti3AlC2 MAX phase, showing its unique blocky morphology. Figure 2 The SEM image in (b) shows that Ti3C2T x MXene has a multi-layer accordion structure. Figure 2 As shown in (c), after hydrothermal treatment, Ti3C2T x TiO2 nanosheets were synthesized in situ on the MXene surface. x W / (001)TiO2 18 O 49 Nanostructures, such as Figure 2 (d) as shown. Figure 8 We demonstrate the direct synthesis of W using a solvothermal method using tungsten hexachloride. 18 O 49 , which presents a unique spindle-shaped morphology. Figure 2 (e) It was confirmed that in Ti3C2Tx / (001)TiO2 / W 18 O 49 PS microplastic particles were successfully captured on the composite substrate surface and in its interlayer structure, providing a basis for subsequent SERS detection. x / (001)TiO2 / W 18 O 49 HRTEM images of the composites ( Figure 2 (f)) and the corresponding element mapping graph ( Figure 2 (il)) clearly reveals that the growth on Ti3C2T x TiO2 nanosheets on the surface and in the layered structure of MXene. In addition, it was observed that x W grown on the surface of MXene 18 O 49 . Figure 2 (g) shows that the crystal spacing of 0.187 nm can be attributed to the (001) plane of anatase TiO2, while the crystal spacing of 0.376 nm can be attributed to W 18 O 49 (010) crystal plane. Selected area electron diffraction (SAED) image ( Figure 2 (h)) shows that TiO2 has (001), (110) and (113) crystal planes. 18 O 49 The presence of (010) crystal plane is consistent with the HRTEM image. Fig. 9 As shown, through EDS element composition analysis, the percentages of carbon (C), titanium (Ti), oxygen (O) and tungsten (W) are 10.92%, 54.41%, 27.42% and 7.26%, respectively.

[0042] Fig.10 Shown Ti3C2T x MXene, Ti3C2T x / (001)TiO2、W 18 O 49 and Ti3C2T x / (001)TiO2 / W 18 O 49 XRD diffraction pattern of the sample. The observed Ti3C2T x The MXene diffraction peaks are consistent with the values ​​reported previously in the literature. x / (001)TiO2 / W 18 O 49In the composite material, the diffraction peaks at 2θ = 25.2°, 38.6°, 53.9° and 62.7° correspond to the (101), (112), (105) and (204) crystal planes of anatase TiO2, respectively (JCPDS No. 21-1272). In addition, the Ti3C2T x The diffraction peaks corresponding to the characteristic (004) crystal plane (17.80°) and (223) crystal plane (60.62°) of MXene indicate that the Ti3C2T x TiO2 with (001) crystal plane exposed was successfully grown on MXene sheets. 18 O 49 The obvious diffraction peaks observed at 23.1° and 47.6° are respectively attributed to the monoclinic W 18 O 49 (010) and (020) crystal planes. x / (001)TiO2 / W 18 O 49 In the composite material, the diffraction peaks at 25.2°, 38.6°, 53.9° and 62.7° are attributed to the (101), (112), (105) and (204) crystal planes of anatase TiO2, respectively, while the peaks at 23.1° and 47.6° correspond to the W 18 O 49 These XRD analysis results confirm that Ti3C2T3 was successfully synthesized by the two-step solvothermal method. x / (001)TiO2 / W 18 O 49 Composite materials.

[0043] Considering that the growth of TiO2 nanosheets with (001) crystal plane exposed depends on the hydrothermal reaction temperature, the reaction temperature was adjusted appropriately. SEM images obtained under 120℃ hydrothermal conditions ( Figure 3 (a) shows that almost no flake TiO2 is formed. This is because the reaction temperature is low, resulting in insufficient oxidation reaction. When the temperature is raised to 140℃, the SEM image ( Figure 3 (b)) shows a multilayer Ti3C2T x TiO2 nanosheets were initially formed on MXene. Figure 3 As shown in (cd), with further increase in temperature, the number of TiO2 nanosheets increases significantly, thus completely covering the Ti3C2T x MXene layer. R6G was used as a probe molecule to investigate the hydrothermal properties of Ti3C2T x / (001)TiO2 substrate for SERS detection. As the temperature increases, the SERS intensity of R6G first increases, then decreases, and reaches a maximum value at 160℃ ( Figure 3 This SERS intensity peak can be attributed to the TiO2 nanosheets and multilayer Ti3C2T x The synergistic effect between MXenes enhances the SERS signal. However, when the reaction temperature exceeds 160 °C, the Ti3C2T x Excessive TiO2 nanosheets grown on MXene cover the SERS active sites, resulting in a decrease in signal intensity. 18 O 49 The loading amount of W is also a key factor affecting the SERS performance. 18 O 49 With the increase of WCl6 dosage, W 18 O 49 The loading amount of WCl6 also gradually increased. When the amount of WCl6 was 60 mg, W 18 O 49 Needle-shaped and completely covered with Ti3C2T x / (001)TiO2( Figure 3 (eh)). Figure 3 As shown in (kl), when the amount of WCl6 is 40 mg, the SERS signal intensity of R6G reaches the best.

[0044] Ti3C2T x / (001)TiO2 / W 18 O 49 Substrate enhancement mechanism

[0045] In this study, we compared Ti3C2T x MXene, Ti3C2T x / (001)TiO2、W 18 O 49 and Ti3C2T x / (001)TiO2 / W 18 O 49 The UV-visible absorption spectra and SERS characteristics of Ti3C2T x / (001)TiO2 / W 18 O 49 SERS enhancement mechanism of Ti3C2T x MXene, Ti3C2T x / (001)TiO2、W 18 O 49 and Ti3C2T x / (001)TiO2 / W18 O 49 The UV-visible absorption spectra of Figure 4 (a). Ti3C2T x / (001)TiO2 absorption peak compared to Ti3C2T x MXene shows a significant red shift. 18 O 49 Compared with Ti3C2T x / (001)TiO2 / W 18 O 49 The absorption of the composite material in the visible light range is significantly enhanced. Figure 4 (b) shows Ti3C2T x MXene, Ti3C2T x / (001)TiO2、W 18 O 49 and Ti3C2T x / (001)TiO2 / W 18 O 49 The detection intensity of the substrate on R6G shows that Ti3C2T x / (001)TiO2 / W 18 O 49 The SERS signal obtained on the substrate is the highest, about W 18 O 49 2.3 times of the substrate, about Ti3C2T x / (001)TiO2 substrate is 6.6 times. To this end, we proposed Ti3C2T x / (001)TiO2 / W 18 O 49 The charge transfer enhancement mechanism of the substrate, e.g. Figure 4 (c) According to literature reports, the band gap of anatase titanium dioxide is 3.18 eV, the conduction band (CB) position is -4.17 eV, and the valence band (VB) position is -7.35 eV; W 18 O 49 The band gap of R6G is 2.92eV, the conduction band position is -5.35eV, the valence band position is -8.27eV, the lowest unoccupied molecular orbital (LUMO) energy level of R6G is -3.40eV, and the highest occupied molecular orbital (HOMO) energy level is -5.70eV. Therefore, the R6G adsorbed on the substrate is similar to TiO2 and W. 18 O 49 The band structures of TiO2 and W can be well matched, providing a pathway for charge transfer between them, which further indicates the SERS enhancement mechanism. 18 O 49VB is excited, and photogenerated holes are generated from W 18 O 49 The VB is transferred to the VB of TiO2 and further transferred to the VB of Ti3C2T x MXene promotes the separation of holes and electrons. The electrons in the CB of TiO2 can migrate to W 18 O 49 In the CB, at the same time, the electrons jump from the HOMO level of R6G to W 18 O 49 CB, while W 18 O 49 The electrons in the CB are excited by light and then transfer to the LUMO energy level of R6G. This effective charge transfer changes the electron cloud density, thus producing chemical enhancement and improving the SERS enhancement effect.

[0046] 3D Ti3C2T x / (001)TiO2 / W 18 O 49 Performance Analysis of SERS Sensors

[0047] The detection sensitivity of SERS sensors is a key parameter to measure their analytical performance. Using R6G as a probe molecule, the three-dimensional Ti3C2T x / (001)TiO2 / W 18 O 49 Sensitivity of SERS sensor. Figure 5 (a) shows the SERS spectra of R6G at different concentrations. The characteristic Raman peaks of R6G are located at 610 cm -1 、769cm -1 、1186cm -1 、1360cm -1 、1509cm -1 and 1648cm -1 As the concentration of R6G solution decreases, the intensity of the Raman peak also decreases accordingly, but even at 10 -8 At low concentrations of M, the R6G peak is still clearly discernible. Fig.11 As shown, the calculated EF value of this sensor is 2.33×10 6 , which indicates that it has high SERS sensitivity. The specific R6G peak is related to the molecular vibration of R6G, 610cm -1 The R6G peak at 769 cm corresponds to the CC in-plane bending. -1 Corresponding to CH out-of-plane bending, 1186 cm -1 Corresponding to the in-plane bending of CH, 1360 cm -1 、1509cm -1 and 1648cm -1Corresponding to the aromatic CC stretching vibration.

[0048] The calculation formula of EF is as follows:

[0049] EF=(I SERS / I BULK )×(N BULK / N SERS )

[0050] Among them, I SERS and I BULK represent the intensities of SERS and normal Raman scattering, respectively, and N SERS and N BULK They represent the number of corresponding R6G molecules effectively excited by the laser beam. According to the above formula, Ti3C2T x / (001)TiO2 / W 18 O 49 The EF of the base is 2.33×10 6 .

[0051] N BULK =(Laser spot area / Diffusion area)×(N A ×Volume BULK ×Concentration BULK );

[0052] N SERS =(Laser spot area / Substrate area)×(N A ×Volume SERS ×Concentration SERS );

[0053] Diffusion area=0.25cm 2 ;

[0054] Substrate area = π(d / 2) 2 =0.5027cm 2 ;

[0055] Volume BULK =Volume SERS ;

[0056] Concentration BULK =10 6 ×Concentration SERS ;

[0057] N BULK / NSERS =(0.5027 / 0.25)×10 6 =2.01×10 6 ;

[0058] I=intensity of the610cm -1 peak;

[0059] I BULK =3447.13au;

[0060] I SERS , Ti3C2T x / (001)TiO2 / W 18 O 49 =3999.03au;

[0061] EF=(I SERS / I BULK )×(N BULK / N SERS )=2.33×10 6 .

[0062] The 3D Ti3C2T x / (001)TiO2 / W 18 O 49 Sensitivity of SERS sensor. 20 μL PS solution of different concentrations was dropped on the sensor surface and SERS detection was performed after it was dried naturally. Figure 5 (b) shows that at 1002 cm -1 、1034cm -1 and 1603cm -1 Three obvious PS Raman characteristic peaks were observed at , corresponding to CC ring breathing vibration, CH plane deformation vibration, and CC stretching vibration. Even when the minimum concentration of PS standard solution was 25 μg / mL, the sensor still maintained its detection ability. The improvement in sensitivity can be attributed to the Ti3C2T x / (001)TiO2 / W 18 O 49 The layered structure of the substrate allows PS to enter the Ti3C2T x / (001)TiO2 / W 18 O 49 It enriches PS on the surface and interlayer structure, thereby improving the detection sensitivity. Figure 5 (c) describes the PS at 1002 cm -1 The linear fitting curve of the SERS intensity at 1002 cm-1 shows that in the concentration range of 25 μg / mL to 1000 μg / mL, the PS-1 The fitting curve of the intensity and concentration at the position shows a strong linear relationship, and the correlation coefficient (R 2 ) value is 0.9906, which indicates that the sensor has the potential to quantitatively detect PS within the tested concentration range. In order to evaluate the signal uniformity of the sensor, 30 points were randomly selected on the sensor surface to collect the SERS spectra of PS. The results are shown in Figure 5 (d) as shown. Figure 5 (e) is 1002cm -1 The scatter plot of the characteristic peak intensity, the calculated relative standard deviation (RSD) value was 12.58%, indicating that the signal uniformity of the entire sensor surface was satisfactory.

[0063] The 3D Ti3C2T was evaluated by bending test. x / (001)TiO2 / W 18 O 49 The durability of the SERS sensor was tested by performing SERS measurements every 50 bends, for a total of 300 bends. This process is important for evaluating the potential of the sensor in practical applications, as the sensor may be affected by mechanical stress. The durability test results are shown in Figure 5 (f) Despite 300 bends, the sensor still shows a high stability at 1002 cm -1 The intensity of the PS Raman characteristic peak at is only reduced by 26.95%, which indicates that the sensor has strong durability.

[0064] These results show that the 3D Ti3C2T x / (001)TiO2 / W 18 O 49 SERS sensors are a promising analytical tool for MNPs detection due to their high sensitivity, signal uniformity, and excellent durability.

[0065] 3D Ti3C2T x / (001)TiO2 / W 18 O 49 Multi-component analysis of SERS sensors

[0066] In actual environmental monitoring, there may be MNPs of various sizes and types. The unique fingerprint recognition function of SERS can be used to accurately distinguish various MNPs analytes at the same time. First, the microsphere dispersions of PS, PE and PP were tested by SERS, and their characteristic Raman spectra were obtained ( Figure 6 (a)). On this basis, the three-dimensional Ti3C2T x / (001)TiO2 / W 18 O 49Multi-component analysis capability of SERS sensors. We performed SERS analysis on two-component mixtures consisting of PS and PE, PS and PP, PE and PP, and three-component mixtures consisting of PS, PE, and PP. The results are shown in Figure 2. Figure 6 (b) By analyzing the specific positions of the characteristic Raman peaks, different types of plastics in these mixtures can be distinguished. x / (001)TiO2 / W 18 O 49 SERS sensors can not only accurately identify a single type of plastic, but also effectively distinguish the components of complex plastic mixtures, highlighting its practical application potential in the field of environmental monitoring and providing strong technical support for environmental protection and MNPs pollution control.

[0067] 3D Ti3C2T x / (001)TiO2 / W 18 O 49 SERS sensors for real-world detection

[0068] In order to verify the three-dimensional Ti3C2T x / (001)TiO2 / W 18 O 49 The ability of SERS sensors to detect MNPs in real environments was investigated. In this study, spiked samples containing PS microspheres were prepared using rainwater, soil, and industrial wastewater, and SERS detection was performed. This evaluation was designed to confirm whether the sensor is suitable for MNPs detection applications under real environmental conditions. The collected rainwater and industrial wastewater samples were untreated, while the soil samples were dispersed and filtered before use. A series of rainwater, soil, and industrial wastewater solutions with different concentrations containing 800 nm PS microspheres were prepared, and 30 μL of each dispersed solution was dropped onto the three-dimensional Ti3C2T x / (001)TiO2 / W 18 O 49 The SERS sensor was then allowed to dry naturally and SERS detection was performed. Figure 7 As shown in the figure, the Raman spectra of PS microspheres in these actual environments are consistent with their intrinsic Raman spectra, which indicates that the sensor can accurately detect MNPs in complex environments. The detection sensitivity of the 3D SERS sensor for all samples is 25 μg / mL, and it shows a good linear relationship in the concentration range of 25 to 1000 μg / mL. 2 These results further confirm that the three-dimensional Ti3C2T x / (001)TiO2 / W 18 O 49The SERS sensor showed strong performance and great potential in detecting MNPs in practical environmental applications. The high sensitivity and good linear response of the sensor make it a powerful tool for environmental monitoring and plastic pollution assessment, which will help to better monitor the environmental risks of MNPs.

[0069] Therefore, the present application provides a Ti3C2T x / (001)TiO2 / W 18 O 49 Composite heterostructure SERS sensor and its application, the sensor has excellent sensitivity, uniformity and durability, Ti3C2T x / (001)TiO2 / W 18 O 49 The layered structure and efficient charge transfer of the SERS sensor can help improve the performance of the sensor. The detection sensitivity of Rhodamine 6G (R6G) is as high as 10 -8 M, and the corresponding enhancement factor (EF) is 2.33×10 6 This high SERS sensitivity enables it to detect polystyrene (PS) microplastic microspheres as low as 25 μg / mL with a relative standard deviation (RSD) of 12.58%. The fingerprint recognition properties of this SERS sensor enable it to detect a variety of MNPs, including polyethylene (PE) and polypropylene (PP), as well as to analyze complex MNPs mixtures. In addition, the sensor can also quantitatively detect PS microplastics in complex environmental samples such as rainwater, soil, and industrial wastewater.

[0070] In the description of this specification, the description with reference to the terms "an experimental example", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the experimental example or example are included in at least one experimental example or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same experimental example or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more experimental examples or examples in a suitable manner.

[0071] Finally, it should be noted that the above experimental examples are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred experimental examples, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A Ti3C2T based x / (001)TiO2 / W 18 O 49 The composite heterostructure SERS sensor is characterized by: Based on Ti3C2T x / (001)TiO2 / W 18 O 49 The preparation method of the composite heterostructure SERS sensor is as follows: Step 1: Dissolve LiF in HCl solution and stir, then add Ti3AlC2, react in a water bath, centrifuge the mixture, wash with deionized water until the pH value of the supernatant is in the range of 6.8-7.2, collect the lower layer Ti3C2T x MXene precipitation and drying to obtain multilayer Ti3C2T x MXene powder; Step 2: The multilayer Ti3C2T x MXene powder was dispersed in 1M hydrochloric acid solution, and NaBF4 was added as a crystal surface control agent. After stirring for 30 minutes, ultrasonic treatment was performed, and the mixture was reacted in a reactor at 160°C for 12 hours. After the reaction, the mixture was cooled and centrifuged. The precipitate was washed with deionized water and dried to obtain Ti3C2T x / (001)TiO2 powder; Step 3: The Ti3C2T x / (001)TiO2 powder was added to the isopropanol solution, WCl6 was added to the obtained suspension, and the mixture was stirred and reacted in the reactor. After the reaction, the precipitate was centrifuged and washed by vacuum filtration to separate Ti3C2T x / (001)TiO2 / W 18 O 49 Filter on a cellulose filter membrane and let it dry naturally. Use a punch to make three-dimensional Ti3C2T x / (001)TiO2 / W 18 O 49 SERS sensor.

2. A Ti3C2T based on claim 1 x / (001)TiO2 / W 18 O 49 The composite heterostructure SERS sensor is characterized by: In step 1, the water bath reaction time is 24 h, the water bath reaction temperature is 35° C., the centrifugation condition is centrifugation at a speed of 3500 revolutions per minute for 5 min, and the drying condition is vacuum drying at 60° C.

3. A Ti3C2T based on claim 1 x / (001)TiO2 / W 18 O 49 The composite heterostructure SERS sensor is characterized by: In step 2, the centrifugation condition is 4000 rpm for 5 min.

4. A Ti3C2T based on claim 3 x / (001)TiO2 / W 18 O 49 The composite heterostructure SERS sensor is characterized by: In step 3, the reaction conditions in the reactor are reaction at 200° C. for 20 h, and centrifugation conditions are centrifugation at 5000 rpm for 7 min.

5. A Ti3C2T based on claim 3 x / (001)TiO2 / W 18 O 49 The composite heterostructure SERS sensor is characterized by: In step three, the specific steps of washing are washing twice with anhydrous ethanol and then washing once with deionized water.

6. A Ti3C2T based method according to any one of claims 1 to 5 x / (001)TiO2 / W 18 O 49 Application of composite heterostructure SERS sensors in microplastics and nanoplastics.

7. A Ti3C2T based method according to claim 6 x / (001)TiO2 / W 18 O 49 The application of composite heterostructure SERS sensor in microplastics and nanoplastics is characterized by: Based on Ti3C2T x / (001)TiO2 / W 18 O 49 The SERS sensor with the composite heterostructure can detect PS particles at a concentration of at least 25 μg / mL and rhodamine at a minimum concentration of 10 -8 M.

8. A Ti3C2T based method according to claim 6 x / (001)TiO2 / W 18 O 49 The application of composite heterostructure SERS sensor in microplastics and nanoplastics is characterized by: Based on Ti3C2T x / (001)TiO2 / W 18 O 49 The composite heterostructured SERS sensor is used to analyze micro / nanoplastic mixtures of PS, PE and PP, and is used for the quantitative detection of PS microplastics in rainwater, soil and industrial wastewater.

Citation Information

Patent Citations

  • Exposed (001) crystal face titanium dioxide / titanium carbide nanosheet as well as preparation method and application thereof

    CN113578355A

  • High capacity electrodes enabled by 2d materials in a viscous aqueous ink

    US20220367853A1